The role of dialogic interaction in EFL writing assessment: A sociocultural perspective - Moradian, Mahmood Reza; Miri, Mowla; Alamdar, Parvin (Indonesian Journal of Applied Linguistics, 2021)
This study investigated EFL writing processes through collaborative assessment from a Vygotskian sociocultural perspective. This study focused on assessing essay writing of one intact group of Iranian EFL learners at the intermediate level of language proficiency (N = 15) based on the placement test administered at the institute. Both learners and their teacher assessed essays based on an analytic scale during seven sessions. Moreover, being engaged in collaborative dialogue, the learners were given the opportunity to discuss existing differences between their self-assessed scores and those assigned by the teacher in order to reach an agreed score. Moreover, all their dialogic interactions were audio-recorded for later transcription and micro-analysis.Â  Findings of the microgenetic analysis revealed that benefiting from the mediatory role of the collaborative dialogue and the checklist, the group under investigation gained insight into their capacities, weaknesses, and their metacognitive awareness was raised as the result of conducting CA. The findings suggested that learners took advantage of the collaborative dialogue in which they were engaged while assessing their writing tasks. In particular, the dialogic interaction afforded the learners the chance to present, discuss, and test their ideas and consequently enhance their awareness of the writing tasks. The collaborative assessment could help the learners gain a better insight into their strengths and weakness; further, it led to their metacognitive awareness about components of a good piece of writing.